Yêu cầu của việc dạy tiếng Việt như một ngoại ngữ = The requirement of teaching Vietnamese as foreign language /Đoàn Thiện Thuật. - Đoàn, Thiện Thuật.
If you want to teach a foreign language such as English or French, you need to learn until you master that language. It is also the case for Vietnamese as a foreign language. However, realities show that this issue is not paid due attention to. Those who disseminate Vietnamese including textbook writers and classroom teachers often think that once Vietnamese is their mother tongue, they do not need to learn it. This is not true because the teaching of Vietnamese is not through the word of mouth but it is the teaching of rules so that the receivers can produce endless expressions of ideas in diversified situations rather than repeating a sentence after the teacher. It is necessary to understand that not all mother tongue speakers are fully aware of the structures of their utterances or the differences between their mother tongue and other languages. The efforts to prepare for the dissemination of Vietnamese as a foreign language lie in the filling of such knowledge deficiency. In other words, the learners need to practice Vietnamese properly to understand the characteristics of the language and culture of the Vietnamese people before and during their teaching and dissemination of the Vietnamese language.Below are some of suggestions on language and culture.